Biota monitoring under the Water Framework Directive: On tissue choice and fish species selection. (April 2018) - Fliedner, Annette; Rüdel, Heinz; Lohmann, Nina; Buchmeier, Georgia; Koschorreck, Jan
Abstract: The study addresses the topic of suitable matrices for chemical analysis in fish monitoring and discusses the effects of data normalization in the context of the European Water Framework Directive (WFD). Differences between species are considered by comparing three frequently monitored species of different trophic levels, i.e., chub ( Squalius cephalus, n = 28), (bream, Abramis brama, n = 11), and perch ( Perca fluviatilis, n = 19) sampled in the German Danube. The WFD priority substances dioxins, furans and dioxin-like polychlorinated biphenyls (PCDD/F + dl-PCB), polybrominated diphenyl ethers (PBDE), α-hexabromocyclododecane (α-HBCDD), hexachlorobenzene (HCB), mercury (Hg), and perfluorooctane sulfonic acid (PFOS) as well as non-dioxin-like (ndl)-PCB were analyzed separately in fillet and carcass and whole body concentrations were calculated. Hg was analyzed in individual fish fillets and carcasses, all other substances were determined in pool samples, which were compiled on the basis of fish size (3 chub pools, 1 bream pool, 2 perch pools). The data were normalized to 5% lipid weight (or 26% dry mass in the case of Hg and PFOS) for comparison between matrices and species. Hg concentrations were generally higher in fillet than in whole fish (mean whole fish-to-fillet ratio: 0.7) whereas all other substances were mostly higher in whole fish. In the case of lipophilic substances these differences leveled after lipid normalization. Significant correlations (p ≤ .05) were detected between Hg and fish weight and age. Hg concentrations varied least among younger fish. PCDD/F, dl-PCB, ndl-PCB, PBDE, α-HBCDD and HCB correlated significantly (p ≤ .05) with lipid concentrations. Fillet-to-whole fish conversion equations and/or conversion factors were derived for all substances except α-HCBDD. Although more data also for individual fish would be desirable the results are nevertheless a step on the way to translate fillet concentrations of priority substances to whole fish concentrations. Graphical abstract: Image 1 Highlights: Levels of 6 priority substances were determined in both, fillet and whole fish. Fillet to whole fish conversion equations and -factors were derived. PCDD/F+dl-PCB, ndl-PCB, PBDE, HCB, α-HBCDD correlated with matrices' lipid contents. Fillet concentrations of Hg and PFOS correlated with levels in whole fish. Lipophilic compounds in fillet correlated with lipid normalized whole fish levels. Abstract : The study addresses the question of tissue choice in biota monitoring and presents fillet-to-whole fish conversion equations and/or -factors for Hg, PFOS, PCDD/F+dl-PCB, ndl-PCB, PBDE, and HCB in freshwater fish.